Utilization of outdoor units as freshwater freezing machines on various masses of salt solution - Mirmanto, M.; Sayoga, I.M.A.; Waasi, A. (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2024)
The effect of solution mass on freezing the freshwater using an AC outdoor unit was investigated. The AC outdoor capacity was ½ PK and the evaporator to absorb the heat from the freshwater was designed in the form of a square spiral placed in a freezing box. The outdoor used R32 as the working fluid. The solution mass variations were 10 kg, 12 kg and 14 kg.   The freezing box was filed with saline solution with a concentration of 20%. The mass of fresh water that was frozen was wrapped in plastic with a mass of water per package of 500 grams. The total mass of the freshwater was 10 kg. The results show that the fastest freezing time occurs at a mass of 10 kg of salt solution with a freezing time of 3.5 hours and the longest freezing time is at a mass of 14 kg of solution with a freezing time of 6 hours. The highest total heat flow rate is 554 W found in the variation of 10 kg solution mass. The AC outdoor unit is very effective to be used as a freezing machine with an EER of 5.8.